A review of the genus Scrobipalpa Janse, 1951 (Lepidoptera, Gelechiidae) in the Afrotropical region - Bidzilya, Oleksiy V. (Zootaxa, 2021)
The genus Scrobipalpa in the Afrotropical region is revised. Thirty-six species are recognized as valid, 20 of which are described as new: S. ochroxantha sp. nov. (South Africa), S. wieseri sp. nov. (Namibia, South Africa), S. turiensis sp. nov. (Kenya), S. wolframi sp. nov. (Namibia), S. natalensis sp. nov. (South Africa), S. varivansoni sp. nov. (South Africa), S. typica sp. nov. (South Africa), S. staudei sp. nov. (South Africa), S. afromontana sp. nov. (Kenya), S. erexita sp. nov. (South Africa), S. admirabilis sp. nov. (Namibia), S. griseata sp. nov. (South Africa), S. nigristriana sp. nov. (Kenya), S. munita sp. nov. (Malawi), S. ochracea sp. nov. (South Africa), S. asantesana sp. nov. (South Africa), S. selectoides sp. nov. (Namibia, RSA), S. etoshensis sp. nov. (Namibia), S. ethiopica sp. nov. (Ethiopia), and S. agassizi sp. nov. (Kenya). Six new synonyms are established: Phthorimaea blapsigona Meyrick, 1916 and Scrobipalpa asiri Povolný, 1980 syn. nov. of Scrobipalpa concreta (Meyrick, 1914); Scrobipalpa xylochroa Janse, 1963 and S. obsoletella hospes Povolný, 1964 syn. nov. of S. obsoletella (Fischer von Röslerstamm, 1841); S. vicaria (Meyrick, 1921) syn. nov. of S. geomicta (Meyrick, 1918); and Gelechia chersophila Meyrick, 1918 syn. nov. of S. portosanctana (Stainton, 1859). The following new combinations for five species previously placed in Scrobipalpa are proposed: Ephysteris cretigena (Meyrick, 1914) comb. nov., Microlechia colasta (Meyrick, 1921) comb. nov., Schizovalva costimacula (Janse, 1951) comb. nov., Gelechia trychnophylla (Janse, 1960) comb. nov. and Trychnopalpa phalacrodes (Meyrick, 1913) comb. nov. Two species, Phthorimaea pendens Meyrick, 1918 comb. rev. and Homaloxestis ocyphanes Meyrick, 1937 comb. rev., are excluded from Scrobipalpa but no current genus is available. The male genitalia of Scrobipalpa nomias (Meyrick, 1921) are described for the first time. All species are diagnosed, some of them are redescribed based on additional material. Identification keys and photographs of adults and genitalia are provided. New or additional host plants are recorded for Scrobipalpa incola (Meyrick, 1912), S. concreta, S. portosanctana, and S. ergasima (Meyrick, 1916). Scrobipalpa incola is recorded for the first time from Namibia, Tanzania, and Kenya; S. concreta is new for Ethiopia, Sudan, Tanzania, Kenya, Mozambique, Benin and Mauritius; S. subroseata for Tanzania and Kenya; S. aptatella (Walker, 1864) and S. biljurshi Povolný, 1980 for Ethiopia; S. obsoletella and S. traganella (Chrétien, 1915) for Namibia; S. geomicta for India and Ethiopia; and S. ergasima for Benin, Zimbabwe, Tanzania, Ethiopia, and Yemen.